The synthesis and reactivity of some hydrocarbyl complexes of iron and ruthenium - Gafoor, Mansoor Ahmed (Department of Chemistry, 2016)
We have reviewed the synthesis and properties of ethylene-bridged dinuclear transition metal complexes. The ethylene-bridged ruthenium complex [CpRu(CO)₂]₂[μ-(CH₂CH₂)] has been prepared. The characterization data (IR, ¹H and ¹³C NMR, and Mass spectral) and properties of this complex are discussed. The crystal structure of this complex has also been determined. The reactivity of this complex with donor ligands (CO, PMe₂Ph and PPh₃), protic acids (CF₃COOH and HCl), bromine, MeOH and with oxidants (Ph₃CPF₆ and AgBF₄) has been investigated. The new ruthenium complexes [{CpRu(CO)₂}₂{μ-(CnH₂n₋₁)}]PF₆ (n = 3 or 5), as well as their known iron analogues have been prepared. The crystal structures of [{CpM(CO)₂}₂{μ-(C₃H₅)}]PF₆ (M = Fe or Ru) have been determined. The fluxional behaviour of the complex [{CpRu(CO)₂}₂{μ-(C₃H₅)}]PF₆ has also been determined and discussed in comparison with the analogous iron complexes. A sequence of reactions of [CpM(CO)₂]₂[μ-(CH₂)₅] (M = Fe or Ru) with Ph₃CPF₆, CF₃COOH and NaI has been shown to give high yields of 1-pentene; the relevance of this reaction sequence is discussed. The synthesis and properties of the known ruthenium ethyl complex [CpRu(CO)₂(CH₂CH₃)] are compared with [CpRu(CO)₂]₂[μ-(CH₂CH₂)]. The synthesis, characterization and properties of the ruthenium haloalkyl complexes [CpRu(CO)₂{(CH₂)nX}] (n = 3, X= Cl, Br or I; n = 4 or 5, X= Br or I) are also described.